A viagem de um leitor: uma investigação semiótica do processo de leitura - Noronha-Taddei, Ana Carolina Cortez (Estudos Semióticos, 2005)
The aim of this paper is to investigate reading as a process. Our corpus is composed by a narrative which brings this process as a fiction, comparing it to a trip. The French Semiotics theory is used to investigate how meaning is built and to conceive reading as a discursive process.